التّناصّ في الخطاب السياسي في القرآن الكريم (دراسةٌ في ضوءِ علمِ اللُّغةِ النَّصّيّ) - حَسَن عبد الحسين الدّلفيّ, عَليّ; عبّود الكنانيّ, ناصر (Journal of College of Education, 2019)
This study aims to investigate the internal and external interrelationships in the political discourse in the Holy Quran by looking at the meanings and how they are transmitted from one text to another. It is considered the most prominent artistic methods used by critics and scholars as a kind of textual interplay and interaction. , And may disappear in two basic types: internal harmony, which is reflected in the interdependence of the text in one text, and its purposes to explain something vague or detail the whole or answer to a question or a definition of the meaning of the possibility or interpretation of the absolute; because the Koran explains each other. As for the external contradiction in the political discourse in the Koran, it is meant to avoid the text of the Koran and other texts, perhaps the most texts close to the Koran text texts of the previous heavenly books, which mentioned many stories and events of the past nations, showing between the texts a bit of compatibility and compatibility, although Hegemony and idolatry in this is the text of the Koran; because of the distortion and falsification, and the reason for the implementation of the wishes of many who wanted religion to be according to their desires and tendencies.